Frailty Status, Not Just Age, is Associated With Postoperative Opioid Consumption: A Retrospective, Population-based Analysis - Kyle R. Latack, MD; Ryan Howard, MD; Mark C. Bicket, MD, PhD; Samantha Cooley, MSW; Vidhya Gunaseelan, MBA, MS, MHA; Michael Englesbe, MD; Jennifer Waljee, MD, MPH, MS (Annals of Surgery Open)
Objective:. To assess the relationship between postoperative opioid consumption and frailty status. Background:. Physiologic reserve can be assessed through both chronologic age as well as measures of frailty. Although prior studies suggest that older individuals may require less opioid following surgery, chronologic age, and frailty do not always align, and little is known regarding postoperative opioid consumption patterns by frailty. Methods:. We conducted a retrospective analysis of opioid-naïve adult patients undergoing common general, vascular, and gynecologic procedures across a statewide quality improvement program from November 6, 2017 to February 28, 2021. Our primary outcome was postoperative patient-reported opioid consumption within 30 days of surgery in oral morphine equivalents (OME). Our primary exposure was frailty status defined by the modified frailty index (mFi-5) criteria. Other covariates included patient demographic and clinical attributes, procedural factors, discharge opioid prescription size, and postoperative complications. Linear regression was performed to assess the association of frailty status and opioid consumption, stratified by age. Results:. In this cohort of 34,854 patients, 10,596 had an mFi-5 score of ≤1 and 3,635 had a score of >1. A score of >1 was associated with increased patient-reported opioid consumption (OMEs 3.3 greater; 95% CI = 1.5–5.1). This held true for individuals over 65 (OMEs 2.7 greater; 95% CI = 0.2–5.1). Frailty status, regardless of score, was negatively associated with an opioid prescription at discharge. Conclusions:. Frailty status is associated with increased opioid consumption after common operations. Future prescribing guidelines and outcomes analyses should consider this marker when reviewing opioid consumption data and related adverse outcomes.